Essential rules of behaviour for police in armed conflict, disturbance and tension : legal framework, international cases and instruments - Crawshaw, Ralph; Holmström, Leif (Raoul Wallenberg Institute professional guides to human rights., 2015)
The primary focus of this book is the laws of war, also referred to as the international law of armed conflict and international humanitarian law. There are two aspects to the laws of war, jus ad bellum, the rules governing resort to armed conflict, and jus in bello, the rules governing the conduct of armed conflict. The purpose of the book is to inform police officials about the latter. It is also written for other State officials, including the military, who may carry out police operations, educators and trainers of police and those who monitor or investigate police or otherwise seek to hold them accountable. In addition to considering rules of behaviour in actual armed conflict, the book focuses on police conduct in those forms of conflict that fall below the armed conflict threshold, that is to say situations of internal disturbance and tension. Whilst the laws of war are not legally applicable in such situations, it is argued here that some of its principles and provisions should form an important element in the strategy and tactics of policing civil disturbances, especially when they are serious in terms of scale or intensity of violence.